Association between Serum C-peptide Level and Diabetic Nephropathy in Type 2 Diabetes Mellitus Patients on Oral Anti-diabetic Drug (Bangladesh Journal of Medical Science, 2023)
Background: Diabetic Nephropathy (DN) treatment focuses mostly on preventing or delaying disease development. The most recent research indicates that C-peptide may have a favourable biological effect on DN. In type 2 Diabetes Mellitus, the link between C-peptide level and DN is poorly understood (DM). The purpose of this study is to evaluate the relation between serum C-peptide and diabetic nephropathy in type 2 DM patients taking an oral anti diabetic medication.Methods: From July 2019 to June 2020, a cross-sectional observational study was done at the Department of Pharmacology and Therapeutics at Dhaka Medical College, Dhaka. A total of 63 randomly selected type 2 diabetes patients met the inclusion criteria. SPSS was used to collect, record, and evaluate biochemical values including FBG, 2hrs ABF, HbA1c, urine for microalbumin, serum creatinine, and serum C-peptide.Result: Among 63 study participants, 40 (63.5%) were female and 23 (36.5%) were male. Mean age of patients was 50.30±10.55 years. Mean duration of DM of total study subjects was 6.29±3.15 years. Out of total study subjects, 17.5% (11) had low serum C-peptide, 74.6% (47) had normal serum C-peptide and 7.9% (5) had high serum C-peptide level. Correlations of clinical and biochemical variables showed negative correlation between serum C-peptide level and microalbumin, DM duration, FBS, 2hrs ABF, HbA1c, creatinine. Mean urine albumin was higher in patients with low serum C-peptide level. The microalbumin level and the duration of DM of study subjects are significantly associated with serum C-peptide.Conclusion: In this study we have found that type 2 diabetic individuals with low serum C-peptide levels have a high frequency of diabetic nephropathy and that serum C-peptide levels are significantly associated with diabetic nephropathy.Bangladesh Journal of Medical Science Vol. 22 No. 04 October’23 Page : 768-772